Levels and trajectories of domain‐specific cognition differ across lifestyle engagement subgroups of older adults. (31st December 2021) - Moored, Kyle D; Parisi, Jeanine M; Snitz, Beth E; DeKosky, Steven T; Williamson, Jeff D; Fitzpatrick, Annette L; Carlson, Michelle C
Abstract: Background: Engagement in lifestyle activities may be neuroprotective, but longitudinal data is needed to best inform health interventions. Characterizing the prospective impact of shared lifestyle activities among older adults may both identify subgroups who could benefit most from intervention and reveal contextual/motivational differences in lifestyle that are relevant to group‐level intervention design. We used latent class analysis to characterize qualitatively distinct lifestyle engagement groups and examined whether they had differential declines in global and domain‐specific cognition. Method: Participants were 3068 individuals from the Ginkgo Evaluation of Memory (GEM) Study who completed neuropsychological testing up to 8 years ( M =5.0, SD =2.4). We assessed 18 physical, intellectual, and social activities using the Lifestyle Activity Questionnaire. Linear mixed effects models adjusted for demographic and health covariates were used to examine lifestyle engagement group differences in cognitive level and changes over time. Result: The four‐class model fit best (Figure 1). The Variety lifestyle group (22%) had high engagement in both intellectual (e.g., taking classes) and social activities (e.g., concerts, church, social clubs). The Intellectual (18%) group had high engagement in intellectual and some social leisure activities (e.g., concerts). The Social (32%) group had high engagement in social institutional activities (e.g., church). Compared to the Least Active (28%) group, the Variety ( B's =.14‐.25, p's <.05) and Intellectual ( B's =.10‐.29, p's <.05) groups had greater levels of cognitive performance across all domains, whereas the Social group was only higher in memory ( B =.11, SE =.04, p =.013; Table 1). The Variety group also had attenuated declines in memory ( B =.02, SE =.01, p =.035) and attention ( B =.02, SE =.01, p =.023) over time. Conclusion: Higher lifestyle engagement, especially in intellectual activities, was associated with higher levels of cognition later in life. Yet, only those with the greatest diversity of activities (Variety group) were protected against subsequent declines in memory and attention. These results extend prior findings that these lifestyle groups differ in risk of incident dementia, by suggesting that memory and attention (vs. visuospatial construction) drive this protective relationship. Our findings also highlight subgroup differences in activity types (e.g., primarily social vs. intellectual) that may lead to more targeted interventions to reduce cognitive declines with age.